Evaluation of polystyrene petri dish-based method for assessing biofilm formation in vitro by Trichosporon spp. and its comparison with test-tube method - Bhattacharyya, S; Hussain, Nusrat; Sarfraz, A; Sengupta, A; Kumar, D; Singh, S (Eastern Journal of Medical Sciences, 2016)
Background: Microorganisms growing in a biofilm are associated with chronic and recurrent human infections and are highlyresistant to antimicrobial agents. There are various methods to detect biofilm production such as tube method (TM) and tissueculture plate method followed by microscopic examination by inverted microscope. Objective: This study was conducted tocompare two methods for the detection of biofilms. Methods: In this study, biofilm formation of ten isolates of Trichosporonspp. by test TM (TTM) and polystyrene petri dish method (PDM) was compared. Results: In the TTM, they were weak biofilmproducers as compared to PDM where they were strong biofilms producers. Conclusion: PDM can be safely used to find outpattern of biofilm formation by Trichosporon.